Analysis of public perception of paid lectures sessions by Ustadz Hanan Attaki and their alignment with Islamic principle - Nurul Inayah; Euis Trisni Sulistyowati; Jeannifer Deni Fernanda; Tiwi Carina Sari; Muhammad Rindu Fajar Islamy (Journal of Islamic Education and Innovation, 2025)
Dakwah has a thousand ways to be done in an effort to spread the teachings of Islam. The phenomenon of Hanan Attaki as a preacher has become a new trend that is followed by the community to be listened to, especially young people who are thirsty for religious insights that are relevant to their lives. This study aims to analyze public perceptions of the phenomenon of paid Islamic lectures conducted by Ustadz Hanan Attaki and their alignment with the principles of Islamic preaching (dakwah). The study employs a descriptive quantitative approach with 30 respondents, consisting of students and Muslim communities in Bandung. Data were collected through online questionnaires to measure respondents' perceptions of paid lectures. The findings reveal that the majority of respondents view paid lectures as aligned with Islamic principles and beneficial for enhancing religious understanding. However, some respondents believe that the commercialization of dakwah may hinder access to religious knowledge, particularly for underprivileged groups. From an Islamic perspective, ensuring inclusivity and fairness in the dissemination of knowledge is a fundamental principle. Solutions such as cross-subsidies can be implemented to ensure equitable accessibility. This study offers new insights into developing a fair and inclusive dakwah approach amidst the phenomenon of commercialization.